Exploring weak intermolecular interactions in thiocyanate-bonded Zn(ii) and Cd(ii) complexes with methylimidazole: crystal structures, Hirshfeld surface analysis and luminescence properties. Issue 42 (29th June 2018) - Di Santo, Alejandro; Pérez, Hiram; Echeverría, Gustavo A.; Piro, Oscar E.; Iglesias, Rodrigo A.; Carbonio, Raúl E.; Ben Altabef, Aida; Gil, Diego M.
Abstract : We report the synthesis, spectroscopy and X-ray crystal structures of four Cd(ii ) and Zn(ii ) coordination compounds with imidazole derivatives and thiocyanate as co-ligands. Abstract : Four new thiocyanate-Zn(ii ) and -Cd(ii ) complexes with 1-methylimidazole (1-MeIm) and 2-methylimidazole (2-MeIm), namely, Zn(1-MeIm)2 (SCN)2 (1 ), Zn(2-MeIm)2 (SCN)2 (2 ), Cd(1-MeIm)4 (SCN)2 (3 ) and polymeric [Cd(2-MeIm)2 (SCN)2 ] n (4 ), have been synthesized and characterized by IR, Raman and UV-Vis spectroscopy. The thermal behavior for all complexes was evaluated by thermo-gravimetric analysis and differential thermal analysis. The crystal structures of complexes1–4 were solved by single-crystal X-ray diffraction methods. A study of intermolecular interactions in the solid state compounds revealed that molecules are linked by weak N–H⋯S and C–H⋯S hydrogen bonds and also by C–H⋯π interaction in the case of structures2–4, which are responsible for the formation and stability of the molecular assemblies. Hirshfeld surfaces and 2D-fingerprint plots allowed us to visualize the intermolecular contacts and their relative contributions to the total surface for each compound. A comparative analysis against similar halogen-bonded complexes was carried out to investigate the tendency of inter-molecular interactions to form contacts in crystals by using the enrichment ratio descriptor. The emission spectra of the free imidazole derivatives and their Zn(ii ) and Cd(ii ) complexes were recorded in acetonitrile solutions. The emissions observed in the spectra of complexes were ascribed to the intra-ligand transitions and ligand-to-metal charge transfer and we have observed an interesting correlation between the fluorescence intensities and C–H⋯π interactions.